2017
DOI: 10.1038/s41598-017-12719-3
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan Disrupts SKN-1/Nrf2-Mediated Oxidative Stress Response in C. elegans and Human Mesenchymal Stem Cells

Abstract: Triclosan (TCS), an antimicrobial chemical with potential endocrine-disrupting properties, may pose a risk to early embryonic development and cellular homeostasis during adulthood. Here, we show that TCS induces toxicity in both the nematode C. elegans and human mesenchymal stem cells (hMSCs) by disrupting the SKN-1/Nrf2-mediated oxidative stress response. Specifically, TCS exposure affected C. elegans survival and hMSC proliferation in a dose-dependent manner. Cellular analysis showed that TCS inhibited the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…These pathways include Nrf2-mediated oxidative stress response, nitric oxide & hypoxia signaling, mitochondrial bioenergetic dynamics, etc. (28-31). Of note, the redox levels and pathways involved in redox signaling have not been thoroughly studied in the differentiating iPS-iCMs.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways include Nrf2-mediated oxidative stress response, nitric oxide & hypoxia signaling, mitochondrial bioenergetic dynamics, etc. (28-31). Of note, the redox levels and pathways involved in redox signaling have not been thoroughly studied in the differentiating iPS-iCMs.…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes the SKN-1 proteins, which are required for longevity and oxidative stress resistance in C. elegans [ 124 ]. There are indeed some similarities between the pattern expression of sod-1 / sod-4 and skn-1 genes after their exposure to the tested compounds ( Figure 5 ), which corresponds with the role of this gene in oxidative stress responses [ 125 ].…”
Section: Discussionmentioning
confidence: 79%
“…In male rats, TCS exposure led to decreases in serum testosterone (T), sperm production, and male accessory gland weight (Kumar, Chakraborty, Kural, & Roy, 2009). Recent studies have also shown that TCS may interfere with thyroid hormone metabolism in humans through the activation of nuclear receptors such as pregnane X receptor (PXR) and constitutive androstane receptor (CAR) (Yoon et al, 2017). In vitro studies also confirmed that TCS exert both estrogenic and androgenic effects in assays with breast cancer cells (Clayton, Todd, Dowd, & Aiello, 2011;Gee, Taylor, & Darbre, 2008) and receptor-based bioassay screens.…”
Section: Introductionmentioning
confidence: 99%